Perancangan Sistem HACCP di PT. X Studi Kasus Pakan Puyuh - Vita Giovanna Dewi Sutanto; Kriswanto Widiawan (Jurnal Titra, 2017)
PT. X is one of animal feed company. PT. X plans to get ISO 22000: 2005 certification. One of the requirements in order to get ISO 22000: 2005 is PT. X must implement Hazard Analysis Critical Control Point (HACCP). Quail feed causes hazards in the stage of production process as flea, fungus, Salmonella sp., Arsenic, Lead, Mercury, Cadmium, aflatoxin, metal, paper, plastic, rope, wooden, over/under scale mixer hence need to design HACCP system. The design of HACCP system is capable of controlling the potential hazards. In addition HACCP as a guarantee of livestock feed quality to meet the demands of consumers. The design of HACCP at PT. X for quail feed products consists of the stages such as making product descriptions, creating process flow diagrams, the seven principles of HACCP, and verification of HACCP design. The hazards that already been analyzed do not include CCP but only Operational Pre Requisite Program (OPRP). Documentation of HACCP consist of Operational Pre Requisite Program (OPRP) Plan documentation. The hazard in the documentation of OPRP Plan is hazard of aflatoxin in the stage of the packing process.